New grass phylogeny resolves deep evolutionary relationships and discovers C4 origins - Aliscioni, Sandra; Smith, Stephen A. (The new phytologist, 2012)
Summary: Grasses rank among the world's most ecologically and economically important plants. Repeated evolution of the C4 syndrome has made photosynthesis highly efficient in many grasses, inspiring intensive efforts to engineer the pathway into C3 crops. However, comparative biology has been of limited use to this endeavor because of uncertainty in the number and phylogenetic placement of C4 origins. We built the most comprehensive and robust molecular phylogeny for grasses to date, expanding sampling efforts of a previous working group from 62 to 531 taxa, emphasizing the C4-rich PACMAD (Panicoideae, Arundinoideae, Chloridoideae, Micrairoideae, Aristidoideae and Danthonioideae) clade. Our final matrix comprises c. 5700 bp and is > 93% complete. For the first time, we present strong support for relationships among all the major grass lineages. Several new C4 lineages are identified, and previously inferred origins confirmed. C3/C4 evolutionary transitions have been highly asymmetrical, with 22-24 inferred origins of the C4 pathway and only one potential reversal. Our backbone tree clarifies major outstanding systematic questions and highlights C3 and C4 sister taxa for comparative studies. Two lineages have emerged as hotbeds of C4 evolution. Future work in these lineages will be instrumental in understanding the evolution of this complex trait.